[latex] \frac{ x^{2}+1 }{x-4} - \frac{ x^{2}-1}{x+3} =23[/latex] [latex] \frac{2}{3-x} + \frac{1}{2} = \frac{6}{x(3-x)} [/latex]

[latex] \frac{ x^{2}+1 }{x-4} - \frac{ x^{2}-1}{x+3} =23[/latex] [latex] \frac{2}{3-x} + \frac{1}{2} = \frac{6}{x(3-x)} [/latex]
Гость
Ответ(ы) на вопрос:
Гость
1) (х² + 1)/( х - 4) - (х² -1)/(х + 3) = 23/1 |·(x - 4)(x + 3) ≠0                                                                x ≠ 4, x ≠-3 (x²+1)(x + 3) -(x² -1)(x - 4) = 23(x + 3)( x - 4) х³ + 3х² + х + 3 - х³ + 4х² + х - 4 = 23(х² - х -12) 7х² + 2х -1 = 23х² -23х - 276 16х² - 25х - 275 = 0 D = 18225 = 135² х1 = (25 + 135)/32 = 160/32= 5 х2 = ( 25 - 135)/32 = -110/32 = -55/16 2) 2/(3 - х) + 1/2 = 6/х(3 - х) |· 2x(3 - x) ≠0                                                  x ≠0,   x ≠3 4x + 3x - x³ = 12 x² - 7x +12 = 0 По т. Виета х1 = 4,  х2 = 3(посторонний корень) Ответ: 4 
Не нашли ответ?
Ответить на вопрос
Похожие вопросы